The search for delicious / Natalie Babbitt. - Babbitt, Natalie (New York : Scholastic Inc, 1969)
The Prime Minister is compiling a dictionary and when no one at court can agree on the meaning of delicious, the King sends his twelve-year-old messenger to poll the country.
G8
Keywords: Fantasy -- Juvenile fiction; Fantasy -- Fiction